Relationship Between Students 'Learning Motivation In Daring Learning With Learning Outcomes In “F&B Service” At SMK Negeri 6 Padang - Rusman, Ferlyan Ningsih; Elida, Elida (Universitas Negeri Padang, 2022)
This research is based on the changes in learning methods in the period of pademi covid-19, namely online learning and still low student learning outcomes in the subject of Meals at SMK Negeri 6 Padang. This research aims to 1) Describe students 'learning motivation in online learning in the subject of Etiquette in SMK Negeri 6 Padang, 2) Describe the learning outcomes of students in the subject of Etiquette in SMK Negeri 6 Padang, 3) Analyze the relationship between students' learning motivation in learning online on the subject of Tata Hidang at SMK Negeri 6 Padang. This type of research is quantitative descriptive with a correlational approach. The population in this study is Culinary students of class XII in SMK Negeri 6 Padang who have studied the Diet of 101 people. Sampling technique by using the method of Simple Random Sampling which amounted to 50 people consisting of 3 classes of the academic year 2020/2021. The data collection technique was performed by using a questionnaire via google from using the Likert Scale which has been tested for validity and reliability first. The results show that there is a positive and significant relationship between students' learning motivation in online learning with the learning outcomes of the subject of Etiquette in SMK Negeri 6 Padang. The relationship between the variables of student learning motivation in online learning with the variables of learning outcomes of the subject of Meals in SMK Negeri 6 Padang is 0.477. So it can be concluded that the hypothesis proposed (Ha) is accepted.